Conservation of Alstroemeria cut flowers stored under refrigeration - Galati, Vanessa Cury; Muniz, Ana Carolina Corrêa; Guimarães, João Emmauel Ribeiro; Mattiuz, Claudia Machado Fabrino; Mattiuz, Ben Hur (Acta Scientiarum. Technology, 2020)
Alstroemeria flowers have shown great importance in the world trade of cut flowers due mainly to its beauty and wide variety of colors. However, the durability of its inflorescences is usually hampered by the rapid yellowing of the leaves, which impairs their decorative quality. Cut flowers require the use of technologies to improve postharvest quality and floral longevity. This research aimed to study the postharvest conservation of inflorescences of Alstroemeria cv. Ajax at different storage temperatures. Floral stems were placed in containers with distilled water and stored at four temperatures (4, 8, 12, and 22ºC) for 12 days. The following analyses were performed: fresh mass variation, respiratory activity, relative water content, soluble and reducing carbohydrate contents, polyphenol-oxidase and peroxidase enzymes, pigments (anthocyanin and carotenoids), and longevity. The experiment was conducted in a completely randomized design, the results were submitted to analysis of variance (ANOVA), and the effect of treatments submitted to F-test. Significant differences were compared using the least significant difference (LSD) at 95% confidence interval (p ≤ 0. 05). The temperatures of 8 and 12ºC were effective in maintaining the postharvest quality of inflorescences during storage period, as they remained turgid due to transpiration reduction caused by low temperatures, and longevity reaching 46 and 22 days, respectively.